Penerapan Klausul Bersyarat dalam Putusan Pengujian Formil Undang-Undang - Faiz Rahman (The Constitutional Court of the Republic of Indonesia, 2022)
Constitutional Court Decision No. 91/PUU-XVIII/2020 became the first formal review decision granting the submission and using a conditionally unconstitutional model. Slightly different from material review, in a formal review, what is declared unconstitutional is the procedure. Consequently, it affects the differences in applying conditionally clauses in a formal review. This research explores the conditionally clauses model used in formal review and its implication. Furthermore, this research illustrates those three clauses are likely always accompanied the conditionally unconstitutional ruling, namely: order to lawmakers to revise the law-making process in a specific period; statement regarding the transitional period of the enforcement of the Law; and statement that the Law will become permanently unconstitutional if no changes are made. Nevertheless, considering the design of formal review in the Constitutional Court Law and implications of conditionally decision in formal review, the appropriateness of conditionally decision model for formal constitutional review need to be reconsidered.